An Acetobacterium strain isolated with metallic iron as electron donor enhances iron corrosion by a similar mechanism as Sporomusa sphaeroides. Issue 2 (15th November 2018) - Philips, Jo; Monballyu, Eva; Georg, Steffen; De Paepe, Kim; Prévoteau, Antonin; Rabaey, Korneel; Arends, Jan B A
ABSTRACT: Sporomusa sphaeroides related strains are to date the only homoacetogens known to increase metallic iron corrosion. The goal of this work was to isolate additional homoacetogenic bacteria capable of using Fe(0) as electron donor and to explore their extracellular electron transfer mechanism. Enrichments were started from anoxic corrosion products and yielded Acetobacterium as main homoacetogenic genus. Isolations were performed with a new procedure using plates with a Fe(0) powder top layer. An Acetobacterium strain, closely related to A. malicum and A. wieringae, was isolated, in addition to a S. sphaeroides strain. The Acetobacterium isolate significantly increased Fe(0) corrosion ((1.44 ± 0.16)-fold) compared to abiotic controls. The increase of corrosion by type strains ranged from (1.28 ± 0.13)-fold for A. woodii to (2.03 ± 0.22)-fold for S. sphaeroides . Hydrogen mediated the electron uptake from Fe(0) by the acetogenic isolates and tested type strains. Exchange of the medium and SEM imaging suggested that cells were attached to Fe(0). The corrosion enhancement mechanism is for all tested strains likely related to free extracellular components catalyzing hydrogen formation on the Fe(0) surface, or to the maintenance of low hydrogen concentrations on the Fe(0) surface by attached cells thereby thermodynamically favoring hydrogen formation. Abstract : Sporomusa and Acetobacterium strains isolated with metallic iron as electron donor enhance Fe(0) corrosion